DOCTORS’ POSTGRADUATE EDUCATION: BASIC CONCEPTS CHARACTERISTICS - Lysenko, Oleksandra (Continuing Professional Education: Theory and Practice, 2019)
This article highlights the basic concepts that reveal the essence of postgraduate training in particular are considered legal documents governing the issue of doctors’ postgraduate education in Ukraine, outlined a wide range of opportunities for doctors’ professional development and postgraduate education. Regulatory sequence stages of professional specialization (internship) and doctors’ professional improvement, including by passing the specialization improvement of information exchange and training as well as training in the workplace defined. The notion of competence, which is defined by the sign of expertise to address specific situations or solving tasks analysed. Postgraduate stage of doctors’ training as a period which is aimed at improving the practical training and formation of readiness for independent medical practice described. Andragogics assumptions are analyzed through the prism of postgraduate training. Feasibility of implementation of modern forms and methods of interactive student-centered learning using distance learning and other tools inherent andragogical educational model in a system of continuous professional development of doctors determined. Self-concept and its importance in the formation of the creative person of the adult learner analyzed. The concept of distance learning described as an opportunity to improve the knowledge and skills of adult learners in a case when they are at a distance from the teacher.